Pengaruh Sustainability Awareness, Risk Perception, dan Digital Investment Platform terhadap Minat Investasi Hijau pada Generasi Z di Indonesia - Meebya Enjelia; Deni Ayu Putri; Ivan Pondra Syahputra; Gamaliel Hendrica.Y.T; Iqbal Prasetyo Darmawan; Sunita Dasman (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
Green investment has become one of the rapidly growing forms of sustainable investment, driven by increasing attention to Environmental, Social, and Governance (ESG) issues. However, Generation Z’s interest in green investment in Indonesia is still influenced by sustainability awareness, risk perception, and the utilization of digital investment technology. This study aims to analyze the influence of Sustainability Awareness, Risk Perception, and Digital Investment Platform on Green Investment Intention among Generation Z in Indonesia. This study employed a quantitative approach using a survey method through an online questionnaire distributed to 100 Generation Z respondents who use digital investment applications. The sampling technique applied was quota sampling, while data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) assisted by SmartPLS 4.1. The findings indicate that Sustainability Awareness and Digital Investment Platform have a positive and significant effect on Green Investment Intention, whereas Risk Perception has a negative and significant effect. Digital Investment Platform was found to be the most dominant variable influencing green investment intention. These findings suggest that strengthening sustainability literacy, investment education, and accessible as well as informative digital investment platforms may enhance Generation Z’s interest in green investment in Indonesia.